GEN Z DIGITAL COMMUNICATION PATTERNS IN LEARNING MANAGEMENT SYSTEM LEARNING - Sri Rahayu, Hilda; Chrisulianti, Rizki; Manafi Albar, Fauzan; Utamie Subiakto, Vania (Universitas Terbuka, 2024)
The impact of the covid-19 pandemic in digital communication, giving new colours in the field of online learning, digital communication patterns are increasingly being applied, especially in the field of education. This has several impacts on students who are accustomed to offline or face-to-face lectures. The purpose of this research is to apply communication patterns in the context of online education through the e-learning Learning management system (LMS) at the Wiyata Indonesia Institute of Management to gen z students, lecturers act as a source of information, the media or technology used acts as a sender, students as recipients, and the goal is student understanding of the messages conveyed, and what are the impacts caused. The research method used is qualitative research method. With a case study approach, this research is field research because the data is obtained directly from the sources, which are five gen z students and one communication science lecturer. The results showed that the communication pattern was categorised as a communication pattern by applying 4 communication patterns, some of these stages were only carried out only during the online learning process. By applying a computer-based communication method through the Learning Management platform, the communication pattern is categorised as a communication pattern by applying 4 communication patterns. Keywords: Communication Pattern, Digital, Learning Management System.